Differentiation of edible fats from selected sources after heating treatments using fourier transform infrared spectroscopy (FTIR) and multivariate analysis - Salleh N.A.M.; Hassan M.S.; Jaafar M.Z.; Juliana Jumal; Farah Wahida Harun (American Institute of Physics Inc., 2024)
Indexed by Scopus